O problema da alienação em Ludwig Feuerbach - Alves, Polliana Pires do Carmo (2002)
The purpose of this dissertation is to discuss the concept of alienation proposed by L. Feuerbach (1804-1872). The concept of alienation was conceived by G. W. F. Hegel (1770-1831) and popularized by K. Marx (1818-1883). Such concept acquired with the German philosopher a semantic ambiguity that lasts up to now. By anthropologyzing the concept of alienation in opposition to the Incarnation of the Verb, Feuerbach subverts the meaning of the Christian mystery, making of the creature the Divine Creator. This work deals with the hypothesis that Feuerbach rationalizes one of the central mysteries of Christianity, the ultimate consequences of the Hegelian method in relation to Christ s Revelation in Absolute. The present investigation led to findings that religious symbols resist more firmly to changes than the traditional mysteries of Chistianism. The result of such a study proved that the Feuerbach process related to this concept of alienation does not reveal the identity of a Christian God.